Las elecciones presidenciales de 1946 y el peronismo naciente vistos por el periódico La Vanguardia - Claudio Panella (Amnis)
The aim of this paper is to give an approach to the way the newspaper La Vanguardia, the official organ of the Socialist Party regarded the rising peronist movement and the general election of 1946. As a result of this electoral contest -the first one free from fraud since 1928- Juan Domingo Perón became a constitutional president of Argentina.This paper will analyze the attitude of the aforementioned newspaper towards the election, the kind of discourse as well as the arguments used to definitely favour the Unión « Democrática » and harshly criticize Perón and his supporting political and social forces. It has been paradoxical to verify how this political scene definitely divorced the mass of workers from left wing political parties - a process that Socialist leaders did not manage to revert - as a consequence of a wrong evaluation of what the Argentine working class of the time needed and desired. It was thus that La Vanguardia, born in 1894 as a « scientific socialist newspaper. Defender of the working class », ended up in 1946 sympathizing with interests that were not exactly the same as the ones workers pursued.